Relationship of Personality Traits, Religious Attitude and Sexual Satisfaction with Tendency Towards Divorcee in Paramedic Females - Fatemeh Ghasemi; Ghasem Askarizadeh; Seyyed Mohammad Hossein Mosavi-nasab (Shahid Beheshti University of Medical Sciences, 2020)
For downloading the full-text of this article please click here. Background and Objective: Because of the growing number of divorces and the destructive effects it may have on the citizens, this study predicted female paramedics' tendency towards divorce focusing on the role of personal Traits, religious Attitude and sexual satisfaction in Kerman. Methods: This is a descriptive correlational study. The statistical population of the study consisted of all married female paramedics in Kerman in 2014-2015, out of which 200 were selected by available sampling method. The instruments used for collecting data included the questionnaire of tendency towards divorce, NEO personality inventory, scale for religious attitude (RAS) and sexual satisfaction scale for woman (SSSW). Descriptive (frequency, mean and standard deviation) and inferential statistics (Pearson correlation coefficient and stepwise and stepwise regression) were used to analyze the data. In this study, all the ethical considerations have been observed and no conflict of interest was reported by the authors. Results: The results of the correlation test showed that religious attitude and sexual satisfaction had a negative and significant relationship with the tendency to divorce. In addition, among the neo-personality dimensions, neuroticism had a positive and significant relationship with the tendency to divorce (r<0.34, P<0.01), and extraversion (r=-0.25, P<0.01) and agreeableness (P<0.01 and r=-0.39) and conscientiousness (P<0.01 and r=-0.41) showed a negative and significant relationship with tendency to divorce. No relationship was found betweenbetween openness (P<0.05 and R=0.10 tendency toward divorce. The most important predictor of divorce was sexual satisfaction (F=362.78, P<0.001). For downloading the full-text of this article please click here. Conclusion: According to the results of this study, caretakers and hospital officials can help to improve the conditions of their employees by holding proper sexual relations training workshops to improve marital satisfaction, as well as increase awareness of the importance of this issue.